(untitled) (Herald of Journalism, 2016)
В статье отмечается роль и значение информации в современном обществе. Автор подчеркивает необходимость и предлагает методы свободного распространения информации. С улучшением социально-экономического положения народ больше интересуется внутригосударственными и зарубежными новостями. Это закономерное явление, подкрепленное Конституционным правом на такие демократические ценности, как свобода слова и плюрализма, при этом спрос на новостные программы не снижается. The article notes the role and importance of information in modern society. The author stresses the need for and methods of offering the free flow of information. With the improvement of socio-economic status, people more interested in domestic and foreign news. This is a natural phenomenon, supported by the Constitutional right to democratic values, such as freedom of expression and plurality, demand on news programs are not reduced.